2004
DOI: 10.1103/physreva.69.022304
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of entanglement in one-dimensional spin systems

Abstract: We study the dynamics of quantum correlations in a class of exactly solvable Ising-type models. We analyze in particular the time evolution of initial Bell states created in a fully polarized background and on the ground state. We find that the pairwise entanglement propagates with a velocity proportional to the reduced interaction for all the four Bell states. Singlet-like states are favored during the propagation, in the sense that triplet-like states change their character during the propagation under certa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
300
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(307 citation statements)
references
References 47 publications
5
300
1
1
Order By: Relevance
“…Despite being mapped into a non-interacting system, the model in the infinite N limit has a rich phase diagram featuring a quantum phase transition [26] at h = 1 and, as far as the entanglement properties are concerned, the divergence of the entanglement range when approaching the curve h 2 + γ 2 = 1, where pairwise entanglement vanishes [27][28][29]. Moreover, its peculiar non equilibrium dynamics has been studied in the framework of dynamical entanglement sharing [30], with periodic boundary conditions assumed. For diagonalizing this Hamiltonian one first maps spin operators σ ± = (σ x ± iσ y )/2 to fermionic operators through the Jordan-Wigner transformation c l =…”
Section: Free Fermionic Systems: Xy Hamiltonianmentioning
confidence: 99%
“…Despite being mapped into a non-interacting system, the model in the infinite N limit has a rich phase diagram featuring a quantum phase transition [26] at h = 1 and, as far as the entanglement properties are concerned, the divergence of the entanglement range when approaching the curve h 2 + γ 2 = 1, where pairwise entanglement vanishes [27][28][29]. Moreover, its peculiar non equilibrium dynamics has been studied in the framework of dynamical entanglement sharing [30], with periodic boundary conditions assumed. For diagonalizing this Hamiltonian one first maps spin operators σ ± = (σ x ± iσ y )/2 to fermionic operators through the Jordan-Wigner transformation c l =…”
Section: Free Fermionic Systems: Xy Hamiltonianmentioning
confidence: 99%
“…We start our analysis by considering again the XY spin bath: the concurrence C(k) in terms of one-point and two-point spin-correlation functions can be analytically evaluated [41,42]. As long as γ = 0, this system belongs to the Ising universality class, for which it has been shown that the concurrence between two spins vanishes unless the two sites are at most next-to-nearest neighbor [36,37].…”
Section: Decoherence and Entanglementmentioning
confidence: 99%
“…These manifest themselves as qualitative changes in the decay of correlations: algebraic in the proximity of a critical point and exponential decay away from it. Entanglement plays a fundamental role in the quantum phase transitions that occur in interacting lattice systems at zero temperature [2,3,4,5,6]. Under these conditions the system is in the ground state, which is also a pure state, and any correlations must be a consequence of the fact the ground state is entangled.…”
Section: Introductionmentioning
confidence: 99%